2019
DOI: 10.3892/mmr.2019.9894
|View full text |Cite
|
Sign up to set email alerts
|

Profiling lncRNA alterations during TNF‑α induced osteogenic differentiation of dental pulp stem cells

Abstract: The multipotent and easily accessible characteristics of dental pulp stem cells (DPSCs) make them a promising target for bone tissue engineering. Long non-coding RNAs (lncRNAs) have an important role in the osteogenic differentiation of mesenchymal stem cells. Nevertheless, whether lncRNAs are involved in the osteogenic differentiation of DPSCs remains unclear. The present study examined the expression alterations of lncRNAs in tumor necrosis factor-α induced osteogenic differentiation of DPSCs. Following iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Studies have confirmed that lncRNAs are also associated with the osteogenic differentiation of DPSCs. Examination of the expression of lncRNAs during TNF- α induced osteogenic differentiation revealed 58 upregulated and 19 downregulated lncRNAs on day 7 and 73 upregulated and 60 downregulated lncRNAs on day 14 [ 181 ]. lncRNA colon cancer-associated transcript 1 (CCAT1) is initially discovered to participate in metabolic, migratory, and proliferative processes in some cancers [ 182 ].…”
Section: Epigenetic Mechanisms In Dpscsmentioning
confidence: 99%
“…Studies have confirmed that lncRNAs are also associated with the osteogenic differentiation of DPSCs. Examination of the expression of lncRNAs during TNF- α induced osteogenic differentiation revealed 58 upregulated and 19 downregulated lncRNAs on day 7 and 73 upregulated and 60 downregulated lncRNAs on day 14 [ 181 ]. lncRNA colon cancer-associated transcript 1 (CCAT1) is initially discovered to participate in metabolic, migratory, and proliferative processes in some cancers [ 182 ].…”
Section: Epigenetic Mechanisms In Dpscsmentioning
confidence: 99%
“…89 lncRNAs were diferentially expressed, 28 upregulated and 61 down-regulated [60]. In another study, osteogenic diferentiation of DPSCs after TNF-α induction, diferentially expressed lncRNAs were detected by RT-PCR after 7 days, and there were 77 (58 increased and 19 decreased) and 133 (73 increased and 60 decreased) diferentially expressed lncRNAs, respectively after 14 days of treatment [61]. Te osteogenesis mechanism of DPSCs regulated by lncRNA can be seen in Figure 3.…”
Section: Lncrnas That Regulate Osteogenic Differentiation Of Dpscsmentioning
confidence: 91%
“…lncRNAs undergo transitional alterations during TNF-α-mediated osteogenic differentiation of pDPSCs, since lncRNA expression patterns differ after 7 and 14 d of treatment with TNF-α. These alterations in lncRNAs expression are predicted to be associated with mRNA alterations at day 7 and 14 posts TNF-α induction[ 97 ]. lncRNA DANCR declines with time during odontoblast-like differentiation of pDPSCs.…”
Section: Epigenetic Regulation Of Dpscsmentioning
confidence: 99%